2015
DOI: 10.9789/2175-5361.2015.v7i1.1975-1986
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HIV in daily life of women living with AIDS

Abstract: Objetivo: Compreender as repercussões do HIV no cotidiano de mulheres vivendo com AIDS. Método: Pesquisa qualitativa com a participação de 11 mulheres usuárias de um centro de Informações em DST/HIV/AIDS e Hepatites Virais de uma cidade do semiárido nordestino, com dados coletados por entrevista semiestruturada e interpretados por análise de conteúdo. Resultados: evidencia-se que o cotidiano de mulheres com HIV/aids sofre repercussões no que refere a sexualidade, pela redução das relações sexuais, descobertas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 6 publications
(11 reference statements)
1
12
0
6
Order By: Relevance
“…Moreover, a study carried out with women with HIV in the state of Bahia showed that the feeling of guilt harmed respondents' social relations and mental health (23) . Guilt is especially prevalent in people with HIV/AIDS when the disease was acquired due to lack of prevention, such as unprotected sex and intercourse with sex workers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study carried out with women with HIV in the state of Bahia showed that the feeling of guilt harmed respondents' social relations and mental health (23) . Guilt is especially prevalent in people with HIV/AIDS when the disease was acquired due to lack of prevention, such as unprotected sex and intercourse with sex workers.…”
Section: Discussionmentioning
confidence: 99%
“…That is why adherence to the therapy and good monitoring is important for them. In Oliveira's article [30], one of the participants states: "It is a responsibility, because you must take that medication, you must have medical monitoring and you must be careful because you can develop some other diseases".…”
Section: Living With the Virusmentioning
confidence: 99%
“…7 Further works have shown that most women have had their sexual activity preserved, although a considerable proportion has become sexually inactive. 8,11 Three publications underlined that most of them either decreased or ceased their sexual intercourse, 9,10,12 besides mentioning the reduction of sexual drive, 10,13 as shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, sexual abstinence and withdrawal from their social environment become part of their routine. 10 A study performed with 161 women living with HIV showed that 72.7% reported psychological, 54.6% physical and 25.4% sexual violence. 16 Those data suggest a higher risk of aggression in HIV-infected women than in those who do not have the virus, then indicating that women bearing HIV have difficulty maintaining their sex life at the same proportion they had before the diagnosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation